THE ROLE OF SYED WAQAR AZEEM IN URDU DASTANI CRITICISM - Dr. Samina Saif; Dr. Nasima Rehman (Zaban-o-Adab, 2022)
Syed Waqar Azeem is considered to be among the preliminary critics and trendsetters in defining the traditions and history of Urdu fiction. The structure of his diverse critical ideologies is basically a blend of literature, civilization, culture, religion and society. He possesses a strong mastery over the different modes of fiction. He does not ignore contemporary consciousness when he makes a critique on fiction. Resultantly, his criticism is not only limited to fiction’s psychological, social, and aesthetic values rather it also mirrors different collections of prose and ideological movements in general and the evolutionary stages of Dastan to Afsana in particular. He has set a standard of fiction through his unbiased and witty beliefs. The critique of Urdu fiction has been introduced with new dimensions due to critical insights provided by him.